De novo 8p21.3→ p23.3 Duplication With t(4;8)(q35;p21.3) Translocation Associated With Mental Retardation, Autism Spectrum Disorder, and Congenital Heart Defects: Case Report With Literature Review - Gug, Cristina; Stoicanescu, Dorina; Mozos, Ioana; Nussbaum, Laura; Cevei, Mariana; Stambouli, Danae; Pavel, Anca Gabriela; Doros, Gabriela (Frontiers in Pediatrics, 2020)
Duplications of chromosome 8p lead to rare genetic conditions characterized by variable phenotypes. 8p21 and 8p23 duplications were associated with mental retardation but only 8p23 duplication was associated with heart defects. 8p22→p21.3 duplications were associated with autism spectrum disorder in several cases. We present a rare case with a de novo duplication of the entire 8p21.3→p23.3 region, documented by karyotype, FISH, and array CGH, with t(4;8)(q35;p21.3) translocation in a 7 years-old girl. She was referred for genetic counseling at the age of 20 months due to mild dysmorphic facial features, psychomotor retardation, and a noncyanotic heart defect. Another examination carried out at the age of 5 years, enabled the diagnosis of autism spectrum disorder and attention deficit hyperactivity disorder. Upon re-examination after two years she was diagnosed with autism spectrum disorder, attention deficit hyperactivity disorder, liminal intellect with cognitive disharmony, delay in psychomotor acquisitions, developmental language delay, an instrumental disorder, and motor coordination disorder. Cytogenetic analysis using GTG technique revealed the following karyotype: 46,XX,der(4),t(4;8)(q35;p21.3). The duplication of the 8pter region and translocation translocated to the telomeric region 4q were confirmed by FISH analysis (DJ580L5 probe). Array CGH showed: arr[GRCh37] 8p23.3p21.3(125733_22400607)×3. It identified a terminal duplication, a 22.3 Mb copy number gain of chromosome 8p23.3-p21.3, between 125733 and 22400607. In this particular case, there is a de novo duplication of a large chromosomal segment, which was translocated to chromosome 4q. Our report provides additional data regarding neuropsychiatric features in chromosome 8p duplication. The phenotypic consequences in our patient allow clinical-cytogenetic correlations, and may also reveal candidate genes for the phenotypic features.